The Distribution of Health Workers in Urban and Rural Health Centers at Tanjung Balai City - Paul Sirait; Sondang Sidabutar; Tatin Wahyanto (Humanistic Network for Science and Technology (HNST), 2020)
The analysis was conducted on all health centers in the working area of Health Office of Tanjung Balai City based on the latest data from PPSDM and Pusdatin Kemenkes RI in 2020. This research using descriptive methods; conducted in February 2020 to April 2020 at the Datuk Bandar Health Center representing urban health centers and Kampung Baru Health Center representing rural health centers. Based on the distribution of health workers in the Datuk Bandar Health Center (urban) in the Health Office of Tanjung Balai City in 2020, the nurses numbered 25 people where the number is excessive 20 people, midwives numbered 13 people where the number is excessive 11 people, and health workers are still less than 2. This is because many health workers moved to the Datuk Bandar Health Center. Based on the distribution of health workers in the Kampung Baru Health Center (rural), the nurses numbered 10 people where the number is excessive 5 people, nutrition workers numbered 2 people where the number is excessive 1 person, and health workers are still less than 2 people. The number of health workers moved from The Kampung Baru Health Center. Keywords: health workers; health center; urban; rural